Análisis Comparativo de los Indicadores Financieros utilizados por la Cooperativa de Ahorro y Crédito CACPE Yantzaza, periodo 2014 - Japón Castillo, Myrian del Rocío (2016)
This thesis entitled "COMPARISON OF financiers INDICATORS analyzes used by the credit union CACPE Yantzaza, PERIOD 2014", it was developed in order to obtain the title of Engineer in Accounting and Auditing CPA, as stated in the art . 151 of the Rules of Academic Board of the National University of Loja. The structure of the thesis is focused on meeting the goals, the same that allowed me to determine the economic and financial situation of the cooperative, serving as a basis for making appropriate decisions that strengthen the efficient development of it. different indicators issued by the Superintendence of Popular Economy and Solidarity (SEPS), in order to evaluate the operation of each of the accounts that make up the financial statements was applied, the calculations was performed with the following results: within the equity capital asset coverage indicator was obtained as a result 1.04%; with respect to asset quality indicator showing gross default percentage of 7% it was performed; coverage provisions for unproductive portfolio with a percentage of 104%; coverage of consumer loans at 105%; coverage microenterprise portfolio 100%; 149% administrative management; 74% degree of absorption; regarding profitability have indicators, operational performance on active ROA giving a result of 2.33%; ROE return on equity with a percentage of 13% and 16% liquidity which means that the cooperative has sufficient resources to meet its short-term obligations. analysis using the PEARLS system which helped a thorough examination of its financial condition was also conducted regarding the protection indicators P1 resulting in 294.17% was applied; within the Financial Structure E1 was used with a percentage of 79.65%; E2 14.13%; E5 63%; E6 15.45%; E7 3.84%; Asset quality in A1 was considered with 2.78%; A2 with a percentage of 13.66%; in Rate of Return and Cost Liquidity R2 is used with 1.12%; R3 with 16%; in relation to financial expenses R5 was used at 1.9%; R6 with 5.5%; R8 with 9%; R9 with 5.4%; R10 with 1.1%; R11 with 0.021%; Liquidity L1 was determined in 39.3%; L3 with 1.52%; in growth signals S10 demonstrated by 30%; S11 -2%. Finally a report of comparative analysis to the indicators used by the cooperative during 2014 which contains their findings and recommendations of the cooperative progress was made. Comparative financial analysis shows more clearly the global view on their investments, productive and non-productive resources and everything related to its financial resources owned by the credit union CACPE Yantzaza.